MATHEMATICS CRITICAL THINKING ABILITY MATERIALS SOCIAL ARRITHMATIC CLASS VII ASSISTED VIDEO ANIMATION IN THE ERA OF COVID-19 - Mely Della Pratiwi; Ratu Ilma Indra Putri; Zulkardi Zulkardi (IKIP Siliwangi and I-MES, 2022)
This study aims to determine students' mathematical critical thinking skills after the implementation of learning using PMRI and LSLC on social Arithmetic material with the help of animated videos in class VII. This type of research is descriptive. The subjects of this study were students of SMP Negeri 1 Palembang class VII.1, totaling 32 students. The data collection technique used is the provision of test questions which amount to 2 questions in the form of descriptions, observations, and interviews. After doing the research, it was found that the mathematical critical thinking skills of class VII.1 students on social Arithmetic material, the subject of sales, purchases, profits, losses, and percentages had appeared a lot. However, some students still did not show indicators of their mathematical critical thinking abilities. The indicators that seem the most are the analytical indicators, while the indicators that appear the least are the interpretation indicators.